The Puma blues - Murphy, Stephen (Dover Publications, Inc., 2015)
"Out of print for nearly 25 years and one of Rolling Stone's Top 50 Non-Super Hero graphic novels of all time, The Puma Blues is a series of interrelated stories that visualize life at the turn of the 21st century as a world of mutated animals, in which a lone government agent investigates the truth behind environmental degradation. Written by Stephen Murphy, the most prolific Teenage Mutant Ninja Turtles author of all time, and illustrated by Michael Zulli, artist on many of the most popular Sandman comics, The Puma Blues unveils "a near-future world kissed by terrorist assaults...and the threat of ecological ruin. Zulli's wildlife art is utterly breathtaking." -- The Comics Journal. Contains adult material."
"Blibliographical note: The Puma Blues: The Complete Saga in One Volume, first published by Dover Publications, Inc., in 2015, is a republication of the following works by Stephen Murphy, and Michael Zulli: The Puma Blues, Book One; the Puma Blues, Book Two; The Puma Blues, number twenty-one, The Puma Blues, number twenty-two; The Puma Blues, number twenty-three; The Puma Blues, number twenty, pp. 44-47; and The Puma Blues, number twenty-four 1/2. A new introduction by Dave Sim and a new Afterword by Stephen R. Bissette have been provided specially for this edition."--Title page verso
Keywords: Umweltschutz; Environmental protection -- Canada -- Comic books, strips, etc; Superhero comic books, strips, etc; Superheld; Kanada; Comic